Obstetric violence in the United States and other high-income countries: an integrative review - Lorraine M. Garcia (Sexual and Reproductive Health Matters, 2023)
Obstetric violence has been documented throughout the world, yet this human rights issue has mostly been investigated in middle- and low-income countries where the intensity and brutality of abuse and mistreatment is more easily recognised as problematic. This integrative review aimed to analyse sources about obstetric violence in high-income countries with the objective of identifying gaps in the research, challenges to the study of obstetric violence, and solutions to framing research that meets those challenges. A systematic search was conducted using the PubMed and CINAHL databases from February to June 2022. Empirical and non-empirical sources, published in English, with no date restrictions, were retrieved. Citation searching was also done. Forty-six sources were included. Identified gaps in the research were: (a) scarce attention to obstetric violence in most high-income countries; (b) most US sources are non-scientific and from outside the healthcare disciplines; (c) inconsistencies in terminology; (d) most studies were conducted with samples of women who had given birth, with scant research about healthcare providers and obstetric violence, and (e) the association between obstetric violence and traumatic birth was under-recognised. Identified challenges to the study of obstetric violence were: (1) factors that enable and perpetuate obstetric violence are multilevel and nonlinear; (2) the phenomenon is contextually complex; and (3) blind spots from routinised harmful practices and normalised mistreatment can prevent healthcare providers and birthing people from recognising obstetric violence. A systems approach and complexity theory are guiding frameworks recommended as solutions to the challenges of studying and correcting obstetric violence.